COMPARATIVE INVESTIGATION OF KNOWLEDGE OF WILD EDIBLE MUSHROOMS IN VARNA REGION WITH OTHER FOREIGN GEOGRAPHIC ZONES - Tsonka Dimitrova; Petko Marinov; Galina Yaneva; Dobri Ivanov (Peytchinski Publishing, 2021)
Purpose: The interest in evaluation of real knowledge of wild edible mushrooms at individual and population level increases mainly in developing countries. The purpose of our inquiry study was to assess the level of knowledge and awareness of the wild mushrooms in a random sample from the population of Varna region in Bulgaria. Material/Methods: We performed an anonymous questionnaire investigation of 200 adult individuals, 100 males and 100 females, from Varna region, including 17 potential opinions from their personal knowledge of wild edible mushroom usage. Statistical data processing was performed using descriptive methods, variation and correlation analyses. Results: Most respondents acquired their knowledge of wild edible mushrooms from their relatives. From all 200 persons investigated 78 respondents were not capable of recognizing at least one wild edible mushroom at all. More respondents trusted other people, who have very good experience with preparation of wild mushrooms, thus relying on differentiation of a mushroom poison. Their awareness was associated with their capacity to properly recognize wild mushrooms as well as their long-term practice to recognize toxic mushrooms. Just a minority of respondents shared that wild mushrooms in their vicinity could be a problem and had a slight idea of mycotherapy. Only two females had heard about training for wild mushroom recognition. There were statistically significant correlation dependences between respondent's awareness of wild edible mushrooms, on one hand, and individual sex status, educational level and main residence, on the other hand. Conclusion: Our study identified two most recognized wild edible mushroom species in Varna region, edible boletus (Boletus edulis Bull) and parasol mushroom (Macrolepiota procera S. F. Gray). Most respondents acquired their knowledge of wild edible mushrooms from relatives. A problem-oriented training of the population on this topic should be performed to improve awareness of common mushroom features and avoid mushroom poisoning.